2015
DOI: 10.15265/iy-2015-011
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Applications for Patient-centered Care Coordination: A Review of Human Factors Methods Applied to their Design, Development, and Evaluation

Abstract: The potential of mobile health applications to assist patients to more actively engage in the management of their care has resulted in a large number of applications being developed. Our review showed that human factors approaches are nearly always adopted to some extent in the design, development, and evaluation of mobile applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 41 publications
(33 reference statements)
0
19
0
2
Order By: Relevance
“…But, the challenges during the development of the healthcare applications have to be the consideration of the real users' needs [26][27][28][29][30]. When the expectations such as reliability, stability, security and accuracy are also important points to be concerned in developing useful healthcare applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But, the challenges during the development of the healthcare applications have to be the consideration of the real users' needs [26][27][28][29][30]. When the expectations such as reliability, stability, security and accuracy are also important points to be concerned in developing useful healthcare applications.…”
Section: Discussionmentioning
confidence: 99%
“…Both versions have been prepared under Android operation system platform, because the majority of mobile device users is based on Android operating system. The user satisfaction for both user interface design [26] and user acceptance were applied [27][28][29][30]. Functions from the first version NMMHA have been improved corresponding to user suggestion which is indicated in Table 2.…”
Section: Non-prescription Medicine Mobile Health Application (Nmmha)mentioning
confidence: 99%
“…Ellesworth et al identified this lack of formal and standardized reporting of EHR usability evaluation results as a major knowledge gap in the field. Similarly, in the rapidly emerging area of patient-centred HIT, evidence on the use and impact of HF methods leaves many questions unanswered especially in relation to 'whether and to what extent' these methods mediate the safe use and positive impact of these technologies [30,31]. As Yardley et al [46] and Kayser et al [47] also pointed out, the extent to which contemporary approaches are adequately engaging patients and capturing their user needs in ways that meaningfully accommodate different levels of technical, textual, and e-health literacy in technology design and implementation remains unclear.…”
Section: Technology Human Factors and Complex Healthcare Environmentsmentioning
confidence: 99%
“…Wildenbos et al [30] and Baysari et al [31] have investigated the extent to which HF knowledge is contributing (or not) to ensuring safe and usable designs and/or reducing unintended consequences for patients as users. Purkayastha et al [32] advocated for finding new ways to tailor approaches in this rapidly expanding area, and Sawesi et al [33] provided a systematic review on the impact of technology on patient engagement and health behaviour change.…”
Section: Introductionmentioning
confidence: 99%
“…Baysari, MT [10] çalışmasında ve Research-2-Rehberlik [11] araştırma raporunda, tahmini olarak 100,000'den fazla M-Sağlık uygulamasının dijital marketlerde yer aldığından bahsetmiştir. Bu sağlık uygulamalarının birçoğu kronik hastalıklar (%31), sağlık ve fitnes (%28) ve sağlık hizmeti (%14) için tasarlanmıştır.…”
Section: Introductionunclassified